Titanium dioxide (TiO₂) and its applications - Parrino, Francesco; Palmisano, Leonardo (Metal oxides series., 2021)
Scientific interest in TiO2-based materials has exponentially grown in the last few decades. Titanium Dioxide (TiO2) and Its Applications introduces the main physicochemical properties of TiO2 which are the basis of its applications in various fields. While the basic principles of the TiO2 properties have been the subject of various previous publications, this book is mainly devoted to TiO2 applications. The book includes contributions written by experts from a wide range of disciplines in order to address titanium dioxide's utilization in energy, consumer, materials, devices, and catalytic applications. The various applications identified include: photocatalysis, catalysis, optics, electronics, energy storage and production, ceramics, pigments, cosmetics, sensors, and heat transfer. Titanium Dioxide (TiO2) and Its Applications is suitable for a wide readership in the disciplines of materials science, chemistry, and engineering in both academia and industry.--